Initial teacher education in the European Space for Higer Education: student opinion (Foro de Educacion, 2024)
This paper reflects a research carried out in the teacher training degrees at the Autonomous University of Madrid. In some of them there has been conducted a pilot project simulating the academic functioning as proposed by the European Space for Higher Education. The correct implementation of the Bologna Process, in any degree, requires establishing some differences in teaching development, namely design, methodology, evaluation and so on. These innovations should be perceived positively by students in order to ensure the actual improvement in academic training at universities and, specially, in the Initial Training of Teachers. This last frame is the object of study of the present research so that we understand the students'  point of view about the implications of the Bologna model on the development of their initial training as future teachers.